Roman dress and the fabrics of Roman culture - Edmondson, J. C.; Keith, Alison Mary (Phoenix. Supplementary volume (Toronto, Ont.), 2008)
"Roman Dress and the Fabrics of Roman Culture investigates the social symbolism and cultural poetics of dress in the ancient Roman world in the period from 200 BCE-400 CE." "The contributors to this volume explore the diffusion of Roman dress protocols in Rome and beyond by looking at Rome's North African provinces in particular, a focus that previous studies have overlooked or dealt with only in passing."--Jacket.